2018
DOI: 10.1016/j.ejphar.2018.02.022
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological inhibition of JAK3 enhances the antitumor activity of imatinib in human chronic myeloid leukemia

Abstract: Imatinib (IMA) is the standard treatment for CML; however, stopping IMA sometimes results in disease relapse, which suggests that leukemic stem cells (LSCs) remain in such patients, even after complete molecular remission has been achieved. Therefore, new strategies will be required to eradicate LSCs. The Janus kinase-signal transducer and activator of transcription (JAK-STAT) pathway is part of the BCR-ABL signaling network, and it is activated in CML, especially in LSCs. JAK2 is known to be associated with C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
(58 reference statements)
0
6
0
Order By: Relevance
“…Among the 11 putative targets, gefitinib, an EGFR inhibitor, was tested in combination with imatinib in K562 CML cell line using MTT cell proliferation assay and was found to have a synergistic antiproliferative activity; EGFR inhibits or reverses imatinib resistance by enhancing the ability of imatinib to bind at the ATP-binding site of Bcr-Abl kinase [40]. The study found that JAK2 and JAK3 had antiproliferative effects on imatinib-resistant BCR-ABL(+) cells [41], and the administration of imatinib plus a JAK inhibitor reduced expression of stem cells markers, enhancing the antitumour effects of imatinib in CML cells [42]. Human ERBB2 is a proto-oncogene that codes for the erbB-2 epithelial growth factor receptor [43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the 11 putative targets, gefitinib, an EGFR inhibitor, was tested in combination with imatinib in K562 CML cell line using MTT cell proliferation assay and was found to have a synergistic antiproliferative activity; EGFR inhibits or reverses imatinib resistance by enhancing the ability of imatinib to bind at the ATP-binding site of Bcr-Abl kinase [40]. The study found that JAK2 and JAK3 had antiproliferative effects on imatinib-resistant BCR-ABL(+) cells [41], and the administration of imatinib plus a JAK inhibitor reduced expression of stem cells markers, enhancing the antitumour effects of imatinib in CML cells [42]. Human ERBB2 is a proto-oncogene that codes for the erbB-2 epithelial growth factor receptor [43].…”
Section: Discussionmentioning
confidence: 99%
“…Administration of the imatinib plus JAK inhibitor reduces the expression of stem cell markers, such as ABCG2 and ALDH1A1. Blocking JAK3 with imatinib and JAK3 inhibitors may represent a new therapeutic strategy for eradicating LSCs and preventing CML recurrence [47].…”
Section: Discussionmentioning
confidence: 99%
“…From another perspective, various studies have investigated the role of the JAK/STAT pathway in the pathophysiology of CML [18, 19]; BCR-ABL activates several signaling pathways such as PI3K, RAF, ERK, MEK, and JAK. The latter transduces signals via STAT and plays essential roles in cell proliferation and differentiation in leukemia [18]. In addition, few in vitro studies have shown that the use of JAK inhibitors with or without imatinib on CML cell lines had a modest positive outcome with JAK2/JAK3 inhibitors alone and a marked effect when combined (synergic effect).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, few in vitro studies have shown that the use of JAK inhibitors with or without imatinib on CML cell lines had a modest positive outcome with JAK2/JAK3 inhibitors alone and a marked effect when combined (synergic effect). This suggests that targeting JAK may carry a potential therapeutic option for CML [1821]. These findings led to the integration of JAK inhibitors in recent recruiting/ongoing clinical trials for treatment of CML (see Web References [22] and [23]).…”
Section: Discussionmentioning
confidence: 99%
“…Leukemia is a type of malignant clonal disease of hematopoietic stem cells, also known as blood cancer, and the mortality rate of patient's ranks sixth in tumor diseases 32,33 . K562 cells are used for the investigation of tumor and leukemia treatment, drug targets and other fields.…”
Section: Introductionmentioning
confidence: 99%